Hi I want check my answer please > look on Attachments
Follow Math Help Forum on Facebook and Google+
L.H.S. $\displaystyle =\frac{\cos^2 z-3\cos z+2}{\sin^2 z}$ $\displaystyle =\frac{(1-\cos z)(2-\cos z)}{(1-\cos^2 z)}$ $\displaystyle =\frac{(1-\cos z)(2-\cos z)}{(1-\cos z)(1+\cos z)}$ $\displaystyle =\frac{(2-\cos z)}{(1+\cos z)}$ =R.H.S.
thanks , but can explain this steps specially the first one
Originally Posted by r-soy thanks , but can explain this steps specially the first one The numerator has been factorised, the denominator has been re-written using the Pythagorean identity.
View Tag Cloud